Edukasi Pajak Kendaraan Bermotor Berbasis Elektronik SAMSAT di Kota Palembang - Azwardi, Azwardi; Igamo, Alghifari Mahdi; Adnan, Nazeli; Yarsah, Waldi Novi; Mardalena, Mardalena (AKM, 2025)
Knowledge about electronic-based motor vehicle tax payments for the millennial generation is very important. Many millennials are still unaware of the importance of paying taxes. With this education, it is hoped that it can help increase public knowledge, especially the millennial generation, to increase awareness of paying taxes. This community service activity was carried out in October 2023 online using the zoom meeting application with a target audience of 50 millennials and students in Palembang City. The results show that the electronic-based motor vehicle tax education activity SAMSAT provides an understanding to gen z and millennials, especially students, regarding the use of the SIGNAL and E-Dempo applications. The contribution of this educational activity can increase participants' awareness of their obligations in paying taxes because it has an important role in the revenue of a country which will later be used to build the country.